The earthquakes effect of fixed jacket platform due to surrounding earthquake in Malaysia - Nor Atiqah, Mohd Sukri (2016)
The suddenness of earthquake that comes without warning seems to bring along unavoidable death, property damage and alter the socioeconomic functioning of the communities involved. Earthquake has caused the destructive of countless city and villages. This nature’s greatest hazards lead to thousands of people were lost their life, living homeless, thus results on adversely impact of country’s economy. The totally unexpected devastation that produces from earthquake may effect on failure of civil engineering structures. The command type of failure usually related on collapse of buildings, bridges, dams, as well as offshore facilities like fixed jacket platform and other structure. Basically almost all civil structure in Malaysia is design without considering effect from earthquake. Moreover, the event of abrupt energy drive within the Earth’s layer which generates seismic waves, which is, will be able to reach pick state enough to extinguish massive structures in additional eradicate countless of lives. The objective of this paper are to study the behavior of fixed jacket platform that subjected to earthquake excitation., to determine the best mode shape of vibration analysis and to determine performance of fixed offshore platform structure under earthquake of determined data location.